Targeting mitochondrial transfer: a new horizon in cardiovascular disease treatment - Baile Zuo; Xiaoyan Li; Dawei Xu; Liping Zhao; Yang Yang; Yi Luan; Bi Zhang (Journal of Translational Medicine)
Abstract Cardiovascular diseases (CVDs) are the leading cause of mortality among individuals with noncommunicable diseases worldwide. Obesity is associated with an increased risk of developing cardiovascular disease (CVD). Mitochondria are integral to the cardiovascular system, and it has been reported that mitochondrial transfer is associated with the pathogenesis of multiple CVDs and obesity. This review offers a comprehensive examination of the relevance of mitochondrial transfer to cardiovascular health and disease, emphasizing the critical functions of mitochondria in energy metabolism and signal transduction within the cardiovascular system. This highlights how disruptions in mitochondrial transfer contribute to various CVDs, such as myocardial infarction, cardiomyopathies, and hypertension. Additionally, we provide an overview of the molecular mechanisms governing mitochondrial transfer and its potential implications for CVD treatment. This finding underscores the therapeutic potential of mitochondrial transfer and addresses the various mechanisms and challenges in its implementation. By delving into mitochondrial transfer and its targeted modulation, this review aims to advance our understanding of cardiovascular disease treatment, presenting new insights and potential therapeutic strategies in this evolving field.